Motywowanie pracowników medycznych - doświadczenia badawcze - Jończyk, Joanna (Motivating Medical Staff - Experimental Studies, 2008)
The paper presents the results of empirical studies concerning motivating medical staff in two independent health care centres from Podlasie region. The analysis concerned such motivational factors as salary, work satisfaction, atmosphere, stability of employment, possibilities of professional development. It has been proved that for medical staff non-financial motivators such as work atmosphere and satisfaction are equally important as salary. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 550-560